ChemInform Abstract: Coleifolides A and B, Two New Sesterterpenoids from the Aerial Parts of Scutellaria coleifolia H.LEV. Issue 2 (23rd December 2015) - Kurimoto, Shin‐ichiro; Pu, Jian‐Xin; Sun, Han‐Dong; Takaishi, Yoshihisa; Kashiwada, Yoshiki
Abstract: isolation and structure elucidation of the title terpenoids (I), which show moderate cytotoxicity against a panel of cancer cell lines